PENGARUH PERPUTARAN MODAL KERJA DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PT HANJAYA MANDALA SAMPOERNA Tbk PERIODE 2014 – 2023 - Rafli Ariani, Muhamad; Puji Astuti, Eni (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of working capital turnover and solvency on profitability. The method used in this research is a descriptive quantitative method. The population in this research is the financial reports of PT HM Sampoerna Tbk for 10 years for the period 2014-2023 which have been recorded and published. The data analysis method in this research uses the Classic Assumption Test, Multiple Linear Regression Test, and Hypothesis Testing using the SPSS 26 approach. The results of this research show that partially the working capital turnover variable does not have a significant effect on the Net Profit Margin at PT HM Sampoerna Tbk , this can be seen in the partial test results of the significance value of the Working Capital Turnover variable of 0.586 which is greater than 0.05 (|-0.586| > 0.05) and tcount < ttable (-0.568 < 2.365) and can be seen in the partial test results of the significance value of The Debt To Asset Ratio variable has a partial effect on Net Profit Margin, with a significant value of <0.05 (0.038 < 0.05) and tcount < ttable (-2.490 > 2.365) while simultaneously Working Capital Turnover and Debt To Asset Ratio have an influence to Net Profit Margin. This can be seen from the significant value of 0.014, which is greater than 0.05 or (0.014 < 0.05), meaning it is significant. Fcount is 8,413 and Ftable is 4.74 so it can be concluded that Fcount (8.413) > Ftable (4.74).